2020
DOI: 10.1016/j.euf.2019.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Value of Nephrometry Scores in Nephron-sparing Surgery: A Systematic Review and Meta-analysis

Abstract: Context: Over the last decade, several nephrometry scores (NSs) have been introduced with the aim of facilitating preoperative decision making, planning, and counseling in the field of nephron-sparing surgery. However, their predictive role remains controversial. Objective: To describe currently available nephrometry scores and to determine their predictive role for different outcomes by performing a systematic review and metaanalysis of the literature. Evidence acquisition: PubMed, Embase1, and Web of Science… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(51 citation statements)
references
References 78 publications
1
48
0
2
Order By: Relevance
“…Our analysis provides some interesting findings that are worth discussing. Not surprisingly, these "very small" masses present lower complexity (a lower RENAL score, a lower rate of hilar tumors, and completely endophytic localization) [15]. Anatomic tumor characteristics are obviously considered in the decision-making process for the management of renal masses.…”
Section: Discussionmentioning
confidence: 99%
“…Our analysis provides some interesting findings that are worth discussing. Not surprisingly, these "very small" masses present lower complexity (a lower RENAL score, a lower rate of hilar tumors, and completely endophytic localization) [15]. Anatomic tumor characteristics are obviously considered in the decision-making process for the management of renal masses.…”
Section: Discussionmentioning
confidence: 99%
“…1). Many studies have shown that RNS is significantly associated with perioperative outcomes and complications [20][21][22][23][24][25]. Another study by Satasivam et al [26] showed that an increase in RNS is associated with histological features of tumor aggressiveness.…”
Section: Renal Nephrometry Scoring Systemsmentioning
confidence: 99%
“…Correlations with WIT, ORT, and percent change in eGFR [21,23,25] Predict the perioperative and postoperative complications; indicate ischemia time [22,25] Predict collecting system entry [23] Associated with the type of surgical approach (open vs. laparoscopic/robotic) and urine leak [24] PADUA Correlated with WIT, ORT, blood loss, and UCS repair [25] Independent predictors of WIT and overall complications [25,27] Predict the perioperative and postoperative complications; indicate ischemia time [22,25,27] Centrality index score Correlations between complexity categories and WIT, ORT, and EBL [21] Associated with WIT [21] Diameter-axial-polar score Estimate the complexity of tumor characteristics better than the RENAL score [29] Associated with kidney volume preservation [31] ABC Associated with EBL, warm and cold ischemia time, and urinary fistula [30] WIT, warm ischemia time; ORT, operation time; eGFR, estimated glomerular filtration rate; EBL, estimated blood loss; UCS, urinary collecting system.…”
Section: Renal Nephrometrymentioning
confidence: 99%
See 1 more Smart Citation
“…Preoperative knowledge of the complexity of a renal mass is the cornerstone for planning a partial nephrectomy (PN) [1]. Given the multiple variables characterizing it – size, length of protrusion from renal parenchyma, longitudinal and coronal location, proximity to the hilum – several nephrometric scoring systems have been proposed during the last decade [2,3]; the RENAL and PADUA classifications are the most widely used of these [4‐6]. Such systems are based, however, on conventional two‐dimensional (2D) imaging rendered as greyscale, which requires a type of cognitive three‐dimensional (3D) reconstruction of a complex structure such as the kidney.…”
Section: Figmentioning
confidence: 99%